2009
DOI: 10.2478/v10101-009-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic endurance of young untrained male and female subjects

Abstract: SummaryStudy aim: To assess the anaerobic endurance of untrained male and female subjects by applying repeated maximal exercises. Material and methods: Untrained male subjects aged 23 -27 years (n = 17, body height 170 -197 cm, body mass 65 -110 kg) and female ones aged 20 -25 years (n = 10, body height 168 -184 cm, body mass 55 -86 kg) performed 6 maximal cycle ergometer (CE) exercises (64 flywheel revolutions each, spaced by 15 s intermissions, the load amounting to 75 g per kg body mass) and 6 bouts of 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In different performance tests for maximal strength and muscle elasticity, females have reached 54-82% of values obtained by males [1,4,5,9,11]. Sienkiewicz-Dianzenza et al [9] reported female-to-male ratio for 6 bouts of 10 push-offs each on an inclined plane device equal 48%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In different performance tests for maximal strength and muscle elasticity, females have reached 54-82% of values obtained by males [1,4,5,9,11]. Sienkiewicz-Dianzenza et al [9] reported female-to-male ratio for 6 bouts of 10 push-offs each on an inclined plane device equal 48%.…”
Section: Discussionmentioning
confidence: 96%
“…Sienkiewicz-Dianzenza et al [9] reported female-to-male ratio for 6 bouts of 10 push-offs each on an inclined plane device equal 48%. Komi and Bosco [1], Hudson and Owen [4] and Nelson and Martin [17] reported female-tomale ratio for height of CMJ equal 58%, 82% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Every coach has to remember that at every stage of training they will come across the problem of gender-based differentiation [4,21,24]. Physical fitness and sexual dimorphism, has been the subject of analysis of numerous research studies [17,20,23]. These research studies indicate that gender is one of the factors which considerably determine success in sport as well as gender-determined characteristic differences manifesting themselves in the combination of morphological, functional, and psychological traits.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrostatic pressure facilitates expiration but exerts some resistance to inspiration; in effect, the strength of respiratory muscles and chest mobility increase. Swimming is an example of the so-called early sports in which high training loads, especially the endurance ones, ought to be applied in the period of growth in order to achieve high results [4,5,10,11,13,20]. Endurance training applied in the pre-adolescence period may increase the ‡O 2 max in swimmers by as much as 20 -30%.…”
Section: Introductionmentioning
confidence: 99%